2008
DOI: 10.1097/med.0b013e328305082f
|View full text |Cite
|
Sign up to set email alerts
|

Work-up and management of paediatric Cushing's syndrome

Abstract: Early diagnosis and treatment of Cushing's syndrome is vital for long-term outcome. The overall prognosis for Cushing's syndrome is good but challenges remain to ensure normal postcure growth and body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
3
32
0
4
Order By: Relevance
“…Although this study confirms the predominance of CD in this age group, previous studies [31,25] have reported higher prevalence rates of pituitary CS.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although this study confirms the predominance of CD in this age group, previous studies [31,25] have reported higher prevalence rates of pituitary CS.…”
Section: Discussionsupporting
confidence: 68%
“…The accuracy of HDDST has been questioned in several studies in adults [31,32,3,19,29] and in children it has been found to lack specificity, in that patients with ectopic CS may also show a degree of cortisol suppression on HDDST [28]. One of our patients with ectopic ACTH demonstrated a 75% reduction in serum cortisol, illustrating the fallibility of the HDDST.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Fakt ten powinien nasunąć podejrzenie organicznego podłoża zaburzeń. Brak skuteczności leczenia antydepresyjnego jest typowym zjawiskiem w zespołach depresyjnych spowodowanych hiperkortyzolemią [3,5,7].…”
Section: Dyskusjaunclassified
“…Takie opóźnienie jest częstym zjawiskiem, według danych z piśmiennictwa w endogennym zespole Cushinga rozpoznanie zwykle jest opóź-nione o 2-3 lata w stosunku do czasu wystąpienia pierwszych objawów [2,5,7,8]. U opisanej pacjentki część objawów, jak bóle głowy i nadciśnienie tęt-nicze, przez długi czas uznawano za psychogenne, a narastającą otyłość i wtórny brak miesiączki wią-zano z wpływem leków antydepresyjnych.…”
Section: Dyskusjaunclassified